Feasibility of remote technical support for electrophysiological ablation procedures during the current COVID-19 pandemic. Issue 1 (25th December 2021) - Müssigbrodt, Andreas; Demoniere, Fabrice; Banydeen, Rishika; Finoly, Steeve; Mommarche, Max; Inamo, Jocelyn
Abstract: Aims: The treatment of heart rhythm disorders has been significantly impacted by direct consequences of the current COVID-19 pandemic, as well as by restrictions aimed towards constraining viral spread. Methods and results: Usually, catheter ablations of cardiac arrhythmias are guided by electro-anatomic mapping (EAM) systems. Technical staff with medical training, or medical staff with technical training, are needed to assist the operator. Travel restrictions due to the current COVID-19 pandemic have limited the in-person availability of technical support staff. To overcome these limitations, we explored the feasibility of a trans-atlantic remote technical support for EAM, with an internet-based communication platform, for complex electrophysiological ablation procedures. Conclusion: Our first experience, based on nine ablation procedures of different arrhythmias, highlights the feasibility of this approach. Remote support for EAM might therefore facilitate continuous care for patients with arrhythmias during the COVID-19 pandemic, particularly in insular settings. Beyond COVID-19-related challenges, this approach will likely play a greater role in the cardiology field in years to come, due to its significant advantages. Graphical Abstract: